2011
DOI: 10.1016/j.jvs.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Successful percutaneous thrombectomy of an infected vena-caval thrombus due to a toothpick

Abstract: We report a case of a 25-year-old Caucasian female with a septic thrombosis in the inferior vena cava (IVC) which contained a toothpick. She was admitted with fever and abdominal pain for 2 weeks. Computed tomography scan showed thrombus with air density in the suprarenal IVC. However, there was no evidence of duodenocaval fistula. Because of the patient's reluctance for surgery, endovascular therapy was tried. A partially-deployed nitinol stent was used as a filter, and aspiration thrombectomy was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…The nearly complete thrombotic occlusion of the inferior vena cava is may be related to a compression of the vein by surrounding inflamed connective tissue that led to an abnormal blood flow. Data in the literature supports this assumption [ 21 , 22 ]. Proposed therapeutic regimens for such an inflammatory thrombus are anticoagulation and drainage of the adjacent abscess [ 22 ] or percutaneous thrombectomy with anticoagulation and antibiotic therapy [ 21 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The nearly complete thrombotic occlusion of the inferior vena cava is may be related to a compression of the vein by surrounding inflamed connective tissue that led to an abnormal blood flow. Data in the literature supports this assumption [ 21 , 22 ]. Proposed therapeutic regimens for such an inflammatory thrombus are anticoagulation and drainage of the adjacent abscess [ 22 ] or percutaneous thrombectomy with anticoagulation and antibiotic therapy [ 21 ].…”
Section: Discussionmentioning
confidence: 77%
“…Data in the literature supports this assumption [ 21 , 22 ]. Proposed therapeutic regimens for such an inflammatory thrombus are anticoagulation and drainage of the adjacent abscess [ 22 ] or percutaneous thrombectomy with anticoagulation and antibiotic therapy [ 21 ]. However, in the case of inflammatory thrombosis secondary to metastatic disease this therapeutic approach is ineffective as demonstrated in the presented case.…”
Section: Discussionmentioning
confidence: 77%
“…Wilner and Carrillo [ 16 ] reported a case of aspiration thrombectomy using the AngioVac suction cannula system (Angiodynamics, Latham, NY, USA) by inserting catheters into the internal jugular vein and femoral vein. Kim et al [ 17 ] published a case in which aspiration thrombectomy was performed through the right common femoral vein while using a half-deployed stent as a filter, which was inserted via the internal jugular vein. Truong et al [ 18 ] reported a case in which mechanical thrombectomy was performed with a combination of a rotatory fragmentation device and a large wire basket while using a half-deployed stent as a filter.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of migration to the aorta, pericardium, coronary artery, lung, liver, portal vein, hepatoduodenal ligament, inferior vena cava, peritoneum, bladder, retroperitoneum, pancreas, kidney, ureter, perianal space, and hip have all been documented [14] . Although migration to other organs was previously described in the English literature direct penetration and impalement of the retro-hepatic vena cava was anecdotally described [15] , [16] , [17] , [18] , [19] , [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%